The Relation of the Majority and Minority of Religious People in Aceh Singkil - Arifin Zain; Syahrin Harahap; Hasan Bakti Nasution (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
Aceh Singkil is one of the districts in Aceh province that has a history of inter-religious conflict. There have been several conflicts here, including in 1979 and in 2015. The conflict not only caused by disharmony but also caused by casualties and moral and material losses. The main problem in this paper is how relations are established between the majority and minority religious communities in Aceh Singkil. This research is a field research with qualitative analysis and data collection techniques used is in-depth non-structured interviews. The results of the study show that socially, the majority and minority religious groups coexist both in the areas of religion, social and culture and life is helping each other. Presumably conflicts arise due to several factors, including the weak enforcement of rules and the establishment of houses that are not in accordance with existing standards.